Inspiring some elements of folk art to prepare contemporary geometric decorative designs (student experiment) - sara mostafa mansor el daposy (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
Folk art is considered one of the richest arts as it expresses the people, their beliefs, their lives and all the patterns of their living behavior and conveyed to us in abundance through art and its decorative elements. Preserving the Egyptian folk cultural heritage is one of the goals of the contemporary artist as he tries to express his artistic and cultural heritage in new and contemporary ways, so the current research By linking the folk arts and the structural systems of engineering grids by investing the principles of engineering in the design of engineering grids, as it is considered one of the broadest structural systems used in the construction of decorative design since ancient artistic times until the present time. The design was done through a student experiment on a sample of design students in the fourth year. The experiment aimed to train students to create decorative designs based on the geometric grid system, through which students can apply the aesthetic rules of design in an easy and simple way. The creation of the grid relied on the elements of Egyptian folk art as a heritage art It is original and was specifically chosen for its simplicity and geometric abstraction and its reduction to details and shade A light that makes its decorative elements suitable as a contemporary decorative geometric grids building unit